PROBLEMA DEMENSIA DALAM PERSPEKTIF YURIDIS - Ratna Winahyu Lestari Dewi (Perspektif, 2002)
Someone who contracts “Demensia” or “senile” will lose his intellectual ability and his social function, as well as decrease his personality and behavior. The scope of decreases include memory, abstract, moral value, impulse control and other cortical disorder. In term of law, a “demensia” patient can be included as law disability (onbeckwam).